Significant Adhesion Reduction with 4DryField PH after Release of Adhesive Small Bowel Obstruction - Ahmad, Mouhannad; Crescenti, Fabio (The Surgery Journal, 2019)
Background Peritoneal adhesions reoccur in up to 100% of cases, possibly causing complications like pain, secondary female infertility, and small bowel obstruction. The latter has a mortality rate of up to 15% during hospitalization. This study investigates if recurrence of peritoneal adhesions can be prevented by prophylactic use of the starch-based medical device 4DryField.Methods The course of 40 patients with surgery for intestinal obstruction and, partially, second intervention was analyzed. In both operations, adhesion severity and extent were scored 0 (no adhesions) to III (massive/dense and vascular adhesions) and 0 (no adhesions) to III (extensive, covering more than approximately 25 × 25 cm), respectively. To prevent recurrence of adhesions all patients were treated with 4DryField gel (60 mL saline solution per 5 g powder), evenly distributed on the whole impaired intestine (including anastomoses) before abdominal closure. Follow-up was up to 1.5 years in a 3 to 6 months' interval.Results Eight patients had relaparotomies on postoperative days 1 to 155. In the first operation, median adhesion severity score was III, median adhesion extent II. In redo-surgeries, significantly lower scores were detected (median adhesion severity: 0, p = 0.0003; median adhesion extent: 0, p = 0.0009). No adverse events related to the product were observed. One patient had later redo-surgery in another hospital due to recurrence of adhesions, one patient suffered from flatulence. All other patients were free of adhesion-related symptoms during follow-up.Conclusion Based on the high severity of diseases and the significant reduction of adhesion severity and extent in redo-surgeries, 4DryField gel is a promising adjunct for adhesion prevention in bowel surgery. The favorable results should be confirmed in prospective randomized trials.
Keywords: ileus; intestinal obstruction; modified polysaccharide; barrier gel; adhesion prevention